Examining pharmacoepidemiology of antibiotic use and resistance in first-line antibiotics: a self-controlled case series study of Escherichia coli in small companion animals - Chan, Olivia S. K.; Lam, Wendy Wing Tak; Naing, Tint; Cheong, Dorothy Yuen Ting; Lee, Elaine; Cowling, Ben; Low, Matthew (Frontiers in Antibiotics, 2024)
Background Clinicians need to prescribe antibiotics in a way that adequately treats infections, while simultaneously limiting the development of antibiotic resistance (ABR). Although there are abundant guidelines on how to best treat infections, there is less understanding on how treatment durations and antibiotic types influence the development of ABR. This study adopts a self-controlled case study (SCCS) method to relate antibiotic exposure time to subsequent changes in resistance patterns. This SCCS approach uses antibiotic exposure as a risk factor, and the development of ABR as an incidence rate ratio (IRR), which can be considered as the multiplicative change in risk for bacteria to become or maintain resistance. Aim: To investigate the IRR of extensive (more than 7 antibiotic classes), revert, persistent, and directed antibiotic resistance according to the duration and type of antibiotic exposures in Escherichia coli (E. coli). Methods and material: We use anonymized veterinary clinical data from dog and cat patients older than 6 months between 2015 to 2020. Patients were considered as suitable cases if they received antibiotics and had minimum of two urinary antibiograms within a 12 month-period (the first prior to antibiotics exposure and the second from 1 week to 6 months after exposure). The first antibiogram is conducted before antibiotic exposure (case n=20). Findings: From 20 individuals and 42 paired antibiograms we found that the IRR = 2 for extensive drug resistance in patients who received short-course antibiotic treatment compared to longer treatments. In contrast, multidrug resistance IRR = 2.6 for long-course compared to short-cacourse antibiotic treatment. The ratio of E. coli isolates that reverted from resistant to sensitive was 5.4 times more likely in patients who received antibiotics for longer than 10 days.